2005
DOI: 10.1370/afm.285
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Continuity of Care and Care Outcomes: A Critical Review

Abstract: PURPOSE We wanted to undertake a critical review of the medical literature regarding the relationships between interpersonal continuity of care and the outcomes and cost of health care.METHODS A search of the MEDLINE database from 1966 through April 2002 was conducted by the primary author to fi nd original English language articles focusing on interpersonal continuity of patient care. The articles were then screened to select those articles focusing on the relationship between interpersonal continuity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
389
3
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(437 citation statements)
references
References 57 publications
18
389
3
12
Order By: Relevance
“…The substantial benefit of interpersonal continuity of care has been reported in a number of studies and is related to better care outcomes (26)(27)(28)(29), including patient enablement (2,4,15). This seems to be important to majority of patients, particularly those from vulnerable groups (27,30).…”
Section: Discussionmentioning
confidence: 97%
“…The substantial benefit of interpersonal continuity of care has been reported in a number of studies and is related to better care outcomes (26)(27)(28)(29), including patient enablement (2,4,15). This seems to be important to majority of patients, particularly those from vulnerable groups (27,30).…”
Section: Discussionmentioning
confidence: 97%
“…In the outpatient setting, greater continuity has been associated with better hypertensive control, lower risk of hospitalization, fewer emergency department visits, higher patient satisfaction, and higher physician satisfaction. [1][2][3][4] Achieving continuity is difficult in the inpatient setting, where care must be provided continuously. Fletcher et al showed that between 1996 and 2006, Medicare patients experienced declining levels of physician continuity during their hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…3 Multiple studies point to the benefits of continuity of patient care, including improved delivery of preventive services, decreased emergency room use, fewer emergent hospital admissions and shorter hospital stays, and better management of chronic diseases. [4][5][6][7][8] Continuity of care also increases patient satisfaction. 9,10 These findings may in part be due to management of illness in a context of trust and respect between physician and patient.…”
Section: Medical Student Educationmentioning
confidence: 99%